Educating the future sonographic workforce: membership survey report from the British Medical Ultrasound Society. (November 2015) - Parker, P C; Harrison, G
The British Medical Ultrasound Society (BMUS), the Consortium for the Accreditation of Sonographic Education (CASE), education providers and the NHS are working together to review how best to develop education for the future sonographic workforce. There is currently a national vacancy rate of approximately 12% across NHS Trusts. Education course placements are often limited to the number of clinical training places available within departments, resulting in a disparity between vacancies and the numbers of qualified sonographers graduating. Clearly there is a need for education to match the service demand. A term often used as a solution to the workforce problem is 'direct entry' ultrasound education. Anecdotally this term has caused confusion amongst health care professionals and as such the aim of this work was to gain an understanding of the views and opinions of BMUS members and interested professionals about direct entry training and subsequent development of any future training programmes. BMUS undertook an online survey with 286 responses. The survey provided insight into the opinions of ultrasound practitioners and the complexities of developing a relevant educational programme for the future sonographer workforce. The results suggested a number of concerns with direct entry ultrasound programmes, including insufficient training places, lack of health care background knowledge, lack of imaging knowledge and no state registration specific to sonographers. Benefits of direct entry to ultrasound training were perceived to be increasing the number of sonographers trained each year, whilst training people in their first choice profession with skills developed specific to the sonographer role. Support for direct entry ultrasound training was limited to 51% of respondents who would advocate this form of ultrasound training if it led to qualified sonographers with the same skills as sonographers exiting from current CASE accredited programmes.